The AcrAB efflux pump contributes to the virulence of Enteroaggregative E. coli by influencing the aggregative behavior - Martina Laudazzi; Emily Schifano; Francesca Sivori; Ludovica Altieri; Daniela Uccelletti; Enea G. Di Domenico; Bianca Colonna; Martina Pasqua; Gianni Prosseda (Frontiers in Cellular and Infection Microbiology)
Multidrug efflux pumps play a major role in the emergence of antibiotic resistance. AcrAB is particularly important among them, as it is the main RND pump in Escherichia coli and other Enterobacteriaceae. In addition to contributing to multidrug resistance, AcrAB also plays a significant role in the virulence of several pathogens. Here, we report that AcrAB contributes to both adhesion to host cells and biofilm formation in EAEC, an enteropathogenic group of E. coli known to cause both acute and persistent diarrhea. EAEC is an emerging pathotype of E. coli characterized by its ability to adhere extensively to epithelial cells in an aggregative manner and to form voluminous biofilms, which favor infection persistence. We found that the deletion of acrB prevents biofilm formation and reduces the export of extracellular DNA (eDNA). By using a specific inhibitor of AcrB, we confirmed the requirement of AcrB transporter activity for biofilm biogenesis. The characteristic aggregative pattern of EAEC is also strongly impaired in the absence of AcrB or in the presence of an efflux-defective AcrB D408A transporter, while it is restored in the ΔacrB strain complemented with acrB. Finally, we show that the EAEC 17-2 ΔacrB derivative is significantly less lethal than the wild type in Caenorhabditis elegans. Complementation with the acrB gene, but not with the acrBD408A allele, fully restores the virulence phenotype after infection. Overall, our results confirm the relevance of the AcrAB efflux pump as a virulence determinant and contribute to understanding the mechanisms adopted by EAEC to form thick biofilms and copious adherence to the epithelial cells, both features enhancing persistence during infections.